KENYATAAN DAN TANTANGAN DALAM KELUARGA MENURUT DOKUMEN AMORIS LAETITIA: SEBUAH REFLEKSI TEOLOGIS DALAM MEMBANGUN KELUARGA KRISTIANI DI ERA MODERNITAS - Supit, Janio; Angwarmase, Evaritus (Pineleng Theological Review, 2025)
The Christian family holds a central role as a living sign of God's love and a tangible manifestation of His plan of salvation. However, amidst modernity marked by secularization, individualism, and moral crises, families face significant challenges that test their vocation as a community of love. Amoris Laetitia (The Joy of Love), a pastoral and theological document by Pope Francis, reflects on the family's call to remain faithful to Gospel values despite the pressures of changing times. This article elaborates on the teachings of the document, focusing on the theological dimensions of unconditional love, forgiveness that builds relationships, and commitment that affirms the family's dignity as a sacred institution. This reflective approach emphasizes the vital role of the Church as a companion and supporter of families in confronting modern challenges, enabling Christian families to become sacraments of love that radiate the light of Christ to the world.